Proposta de formação continuada do professor de Língua Portuguesa na perspectiva da escrita processual - Parro, Marianna Zaroni (2024)
This research was motivated by the concern that the Portuguese teacher training aimed at text production is often not based on the perspective of writing as a process. Consequently, many teachers adopt teaching models focused on standard grammar and apart from the uses of language. The main objective of this study is to discuss the principals underlying Portuguese teachers continuous training on writing as a process, and to develop, through such discussion, a training proposal with theoretical-methodological procedures that enable the discussion about the concept of teaching and learning writing as a process. Aimed at middle school Portuguese teachers, specific objectives are: (1) to find out 6th grade Portuguese teachers’ training needs to teach writing; (2) to present a training proposal that approaches the teaching and learning of writing as a process. Theoretical framework on teachers’ continuous training and their training needs is grounded on the ideas of Berbaum (1982), Marcelo García (1999), Medina & Domínguez (1989), Libâneo (2000), Placco & Souza (2015), Placco & Souza (2018), Perrenoud (2002), Pimenta (2002), and Tardif (2002). The teaching of writing is based on the studies of Abaurre & Abaurre (2012), Colello (2007), Lajolo & Zilberman (1982), Lerner (2002), Cintra & Passarelli (2012), and Passarelli (2002; 2012). The perspective of multiliteracy, by Rojo (2009; 2013), the four pedagogical movements of the Multiliteracy Pedagogy by the New London Group in Liberali et al. (2015), and NLG (2021), as well as the reflexive methodology, by Schön (2000), and the reverse planning, by Wiggins & Mctighe (2019), are the framework of the training proposal developed. Research methodology is based on content analysis and prose analysis, respectively by Bardin (1977) and André (1983), as well as on Severino (2007), Bauer & Gaskell (2002), and Gatti (2005), using a semi-structured interview in a focal group to collect and analyze teachers’ training needs. The results of this research add up to teachers’ efforts to develop students’ writing skills, in a way to promote discussion on the concept of teaching writing, and the importance of enhancing the position of the reflexive teacher